THE INFLUENCE OF TAX MORALITY AND THE RISK OF PENALTIES ON MOTOR VEHICLE TAXPAYER COMPLIANCE THROUGH TRUST LEVELS AT THE DOMPU REGENCY SAMSAT OFFICE - Ghina Devina Aulia Putri; Chairul Adhim; Firmansyah Firmansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to assess the impact of tax ethics and the potential for penalties on the compliance of motor vehicle taxpayers through trust as a mediating variable at the Dompu Regency Samsat Office. The method used in this study is quantitative, with a population comprising all motor vehicle taxpayers in Dompu Regency, the exact number of whom is unknown. Sampling was conducted using accidental sampling, resulting in a total sample of 97 respondents. Data were collected via an online questionnaire distributed using Google Forms. For data analysis, Partial Least Squares-based Structural Equation Modeling (PLS-SEM) was employed to test the measurement model (outer model) and the structural model (inner model), as well as to conduct hypothesis testing. The research findings indicate that tax morality has a positive and significant influence on taxpayer compliance, while the risk of sanctions does not show a significant influence on such compliance. Furthermore, trust does not significantly influence taxpayer compliance and cannot mediate the relationship between tax morality and the risk of sanctions on taxpayer compliance. Therefore, tax morality is the key factor with the greatest impact on improving compliance among motor vehicle taxpayers in Dompu Regency.